What the Aftermath of the Global Pandemic Will Mean for Neurologists - Stela Rutovic; Ekaterina Volevach; Hana Maršálková; Ana Isabel Fumagalli; Francesco Corea (MDPI AG, 2021)
The emergence of the Coronavirus disease (COVID-19) pandemic caused by the SARS-CoV-2 virus has had a widespread public health impact, thus causing a significant socioeconomic burden [...]